Transoral Robotic Surgery in Retrostyloid Parapharyngeal Space Schwannomas - Ansarin, Mohssen (Hindawi Publishing Corporation, 2014)
Parapharyngeal space (PPS) tumors are very rare, representing about 0.5% of head and neck neoplasms. An external surgical approach is mainly used. Several recent papers show how transoral robotic surgery (TORS) excision could be a prospective tool to remove mainly benign lesions in PPS; no cases of neurogenic tumors from the retrostyloid space treated with TORS have been reported. We present two cases which underwent TORS for schwannomas from the retrostyloid compartment of the parapharyngeal space. Clinical diagnosis of schwannoma was performed by magnetic resonance imaging (MRI). In the first case a 6 cm neurogenic tumor arose from the vagus nerve and in the second case a 5 cm mass from the sympathetic chain was observed. Both cases were treated successfully by the TORS approach using a new “J”-shaped incision through the mucosa and superior pharyngeal constrictor muscle. Left vocal cord palsy and the Claude Bernard Horner syndrome, respectively, were observed as expected postsurgical sequelae. In case 1 the first bite syndrome developed after three months, while no complications were observed in case 2. Both patients regained a normal swallowing function. TORS seems to be a feasible mini-invasive procedure for benign PPS masses including masses in the poststyloid space.